Penyelesaian Persamaan Non Linear Dengan Metode Bagi Dua dan Posisi Palsu Menggunakan Excel Dan Matlab - Utami Fitriani; Salsabilla Ahadiyyah; Ari Wibowo (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
This study aims to compare and evaluate the effectiveness of the Bisection Method and the False Position Method in solving non-linear equations using Excel and MATLAB software. Through literature studies and practical implementations, this study analyzes the characteristics of each method. Evaluations are carried out on the convergence, accuracy, and computational efficiency of both methods on both platforms. A case study of the non-linear equation x = 2x2 + 3x - 5 is solved by both methods in Excel and MATLAB. Based on the numerical method applied, the approximate roots for the non-linear equation are obtained. The results show that the Bisection Method produces the root of x = 0.999878 after 15 iterations, while the False Position Method provides faster convergence results by producing higher accuracy, namely producing the root of x = 0.999940 in only 10 iterations with an error tolerance of 0.0001. The implementation in Excel is done by compiling an iteration table, while MATLAB automates the iteration process. Thus, the False Position Method is superior in convergence speed compared to the Bisection Method. This study provides comprehensive insights into the application of numerical methods in solving non-linear equations and the factors that influence the performance of the methods in different computing environments. Keywords: Bisection Method, False Position Methot, Non-Linear Equations, Excel, Matlab